School Community Empowerment as A Minority Group in Republic Gubuk Library - Inawati, Inawati; Dewi, Amalia Nurma; Setiawan, Setiawan; Martutik, Martutik; Rizqi, Aminah; Azizah, Nur; Hasna, Natasya (Universitas Pendidikan Indonesia, 2022)
This study aims to analyze the form of empowerment of the dropout community as a minority group in Society-based Library Republik Gubuk. The method used in this research is qualitative data analysis with a case study approach. Data were collected using interview techniques and direct observation at Society-based Library Republic Gubuk. The results of the study showed that several work programs of Society-based Library Republik Gubuk in empowering minority groups, especially children who dropped out of school, by providing space to be creative and innovate according to their respective interests and talents as human resource management activities to have skills and be able to compete. Along with the times. The Society-based Library Republik Gubuk work program provides training in honing creativity as a provision in improving skills based on groups of interest. These activities are called